Jozef Schreier "On finite base in topological groups'' - Ya. Prytula; I. Guran (Математичні Студії, 2013)
One of the Ph.D. students in mathematics that belonged to Lviv Mathematical School of1920–1939 years is J´ozef Schreier. In the article, the authors provide an overview of main resultsof the unpublished thesis “On finite base in topological groups” by J´ozef Schreier as well as theconnection of the ideas of this work with modern investigations in the theory of topologicalgroups and semigroups.